IDENTIFICATION OF BUSINESS OPPORTUNITIES WITH THE UTILIZATION OF CORN PLANT WASTE (ZEA MAYS L.) IN EAST LOMBOK DISTRICT - muhammad anwar; Rini Endang Prasetyowati Prasetyowati; Idiatul Fitri Danasari; Dwi Haryati Ningsih (Journal of Agri Rinjani: Social Agricultural Economics - Faculty of Agriculture, UGR, 2021)
The success of agricultural development, especially in East Lombok Regency, depends on the success of optimizing the utilization of its natural resources. One of the reasons for the acceleration of GRDP growth rate in 2017 was a significant increase in the Agriculture, Forestry and Fisheries categories. East Lombok Regency has a productive land area of ​​22,560 hectares for corn plants with a production of 145,319 tons/year. Almost all parts of the corn plant can be used for various purposes. The young stems and leaves are used as animal feed and organic fertilizer, corn cobs as bioethanol and briquettes, and corn husks as handicraft materials. From each corn harvest, it is estimated that around 65% of shelled corn (rendemen) is produced, while 35% is in the form of waste in the form of stems, leaves, husks, and corn cobs. The focus of this paper is on the utilization of corn plant waste in East Lombok Regency as a business opportunity that can create a product that has economic value. This research method uses descriptive qualitative with a literature study approach. Various business opportunities can be carried out by utilizing corn plant waste into various products, such as: (1) Corn straw as a good source of animal feed for the growth of ruminants and the basic ingredients for making organic fertilizers, (2) Corn cobs and husks as basic ingredients for making various types of handicrafts, as bioethanol (raw material for chemical, cosmetic, pharmaceutical, and as fuel), and as alternative fuels (syngas and briquettes).